Gross morphological studies on major salivary glands of prenatal buffalo - Raja, K.; Lakshmi, M. Santhi; Purushotham, G.; Raghavender, K.B.P.; Rao, T.S. Chandrasekhara; Kumar, D. Pramod (Buffalo Bulletin, 2016)
Gross morphological study was conducted on the major salivary glands of 42 buffalo foetuses ranging from 73 to 253 days. The mandibular gland was the largest salivary gland during the prenatal life. Dense compact lobulation of the parotid and mandibular glands was observed first at 155 days of foetal age. The mandibular gland was covered by the confluence of linguo-facial, occipital and maxillary veins laterally and developing thymus caudally throughout the prenatal period. Differentiation of dorsal and ventral parts of the sublingual gland was observed at 108 days of foetal age. Major salivary glands of various domestic animals are paired structures, which includes parotid, mandibular and sublingual glands. Salivary glands fulfill important role in the oral biology by producing saliva for lubrication, as well as supplying electrolytes, mucus, antibacterial compounds and various enzymes to the oral cavity. Loss of salivary glands function can result in the wide spread deterioration of oral health (Hsu et al., 2010). Study of normal development of salivary glands will be helpful for both anatomists and clinicians as they are having important role in several dreadful diseases like rabies, foot and mouth disease and other viral diseases. Keywords: buffaloes, Bubalus bubalis, Gross morphological, salivary glands, mandibular duct